2015
DOI: 10.1186/s13570-015-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Participatory analysis of vulnerability to drought in three agro-pastoral communities in the West African Sahel

Abstract: Drought is one of the major climatic hazards impacting on the various sectors including crop and livestock in the West African Sahel. Pastoral and agro-pastoral communities in the region are regularly affected by drought, with vulnerability differing with gender, age, wealth status (access to cropland and livestock endowment), geographic location, social networks, and previous exposure to drought. Effective interventions require regular monitoring of vulnerability to drought, for which various quantitative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Assessment of drought risk 3.3.1. Assessment approaches The review of existing drought risk assessments revealed that the majority of studies applied quantitative (56%) or mixed-methods (32%) approaches, while purely qualitative approaches are rather rare (11%) and have mostly been applied at the subnational level with results extrapolated to explain phenomena at broader spatial scales (Nelson and Finan 2009, Saha et al 2012, Ayantunde et al 2015, Birhanu et al 2017.…”
Section: Conceptualization Of Drought Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of drought risk 3.3.1. Assessment approaches The review of existing drought risk assessments revealed that the majority of studies applied quantitative (56%) or mixed-methods (32%) approaches, while purely qualitative approaches are rather rare (11%) and have mostly been applied at the subnational level with results extrapolated to explain phenomena at broader spatial scales (Nelson and Finan 2009, Saha et al 2012, Ayantunde et al 2015, Birhanu et al 2017.…”
Section: Conceptualization Of Drought Riskmentioning
confidence: 99%
“…Meanwhile, Martin et al (2016) apply a processbased, spatially-explicit social-ecological model for analyzing system dynamics contributing to drought risk for pastoral households in Morocco. In contrast, Ayantunde et al (2015) use qualitative methods (FDGs, community workshops, seasonal calendars, etc) to analyze the patterns and causes of drought risk in three agro-pastoral communities in Western Africa.…”
Section: Conceptualization Of Drought Riskmentioning
confidence: 99%
“…The conceptual diversity in CCVA studies also predisposes research to follow specific methodological approaches (Ford et al 2010;Singh et al 2017;Adamson et al 2018). These include qualitative case study-based methods (Campeanu and Fazey 2014;Joakim et al 2015), spatially mapping vulnerability hotspots (Varadan and Kumar 2015;Bouroncle et al 2016), indicatorbased assessments (Hahn et al 2009;Gupta et al 2010;Gerlitz et al 2017), participatory methodologies that co-produce adaptation solutions (van Aalst et al 2008;Fazey et al 2010;Howe et al 2013;Ayantunde et al 2015;Butler et al 2016), and more recently, historical and temporal approaches to examine trajectories of change (Nielsen and Reenberg 2010;Fawcett et al 2017;Adamson et al 2018;Gajjar et al 2018). This methodological diversity is detailed in Supplementary Material 1.…”
Section: Current Methodological Approaches To Climate Vulnerability Amentioning
confidence: 99%
“…This debate reflects and reinforces, through abstraction, the exclusion of alternative, context-specific ways of knowing (Eriksen et al, 2015;Shah et al, 2017). The extended experiences with climate variability and change held by dryland African communities, such as those of the Maasai mentioned above or the Fulani herders of the West African Sahel who have been experiencing changing climatic conditions for decades, are ignored, or at least reduced and repackaged, within these dominant frameworks as the global community seeks to make sense of the novel experience of more directional climate change (Ayantunde, Turner, & Kalilou, 2015;Ericksen et al, 2012;Martin, Müller, Linstädter, & Frank, 2014;Smith, Barrett, & Box, 2000). Because human dimensions scholarship should be about how people make sense (shaping response) of the changes they experience, the discursive framing of peoples' experience can be highly misleading, particularly when it excludes experiences with climate variability that do not "fit" climate model projections.…”
Section: Discourse: Human Dimensions Of Climate Changementioning
confidence: 99%